Bioaccumulation of PBDEs and PCBs in a small food chain at electronic waste recycling sites. Issue 1 (2nd January 2017) - Han, Zhao-Xiang; Wang, Ning; Zhang, Hai-Liang; Zhao, Yu-Xia
ABSTRACT: Soil, rice plant, and animal samples were collected from an e-waste recycling area to investigate the levels and bioaccumulation extent of polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) released from e-waste that was processed using crude recycling methods in Changzhou, China. ∑PBDE and ∑PCBs levels of soils were significantly higher at the e-waste dismantling areas than those from residential areas. PBDEs in soils resulted in their increasing accumulation in rice plants. Median values of ∑PCBs in the sampling species were 120–12120 ng/g wet weigh (ww), and the Cplan t / Csoil values for BDE-28 and PCB-28 were one order of magnitude greater than those for BDE-209 and PCB-180, respectively. Moreover, distributions of PBDE and PCB congeners in rice plants were very similar, even among different sampling sites. ∑PBDEs and ∑PCBs had the highest BMF values at the investigated sites. Therefore, in addition to commercial PBDEs and PCBs, their debromination products should be another concern in assessing the adverse influences of PBDEs and PCBs on the environment and human health.